Linguagem de adolescentes sob medidas socioeducativas em meio aberto: uma abordagem fonoaudiológica - Alencar, Isabela Barros Gonçalves (2017)
The purpose of this research was to raise aspects of language, especially adolescent speeches under socioeducational actions in an open environment to problematize pathological notions and/or social disqualification arising from eventual singularities of the repertoire and the enunciation forms of these people. It was held at CEDECA-Madalena. The people were nine adolescents who comply with measures in the institution, aged between 15 and 18 years. Data collection was performed through three complementary strategies: a) semi-structured interviews with adolescents; B) application of the Mini Mental State Examination (MMSE) with adolescents; C) an open interview with employees. The results pointed to peculiar aspects of adolescents' language and speech, according to their living conditions and sociability. The results of the MMSE did not show signs of language disorders in that group of research, with exception of one adolescent, who scored slightly below their educational level, but without discursive alteration. Adolescents were critical of their ways of speaking, assigning negative value to the use of slang and metalanguage proper to social groups (including marginality), as if these uses of language were inferior and, therefore, have forbidden from move in other social spheres. It could be concluded that adolescents in compliance with socio-educational actions in the open environment may present low self-image in relation to their ways of speaking and/or writing, referring to them as not acceptable in society in general, which would generate obstacles to the circulation and Social integration